Completion of annual diabetes care processes and mortality: A cohort study using the National Diabetes Audit for England and Wales. Issue 12 (1st September 2021) - Holman, Naomi; Knighton, Peter; OʼKeefe, Jackie; Wild, Sarah H.; Brewster, Sarah; Price, Hermione; Patel, Kiran; Hanif, Wasim; Patel, Vinod; Gregg, Edward W.; Holt, Richard I. G.; Gadsby, Roger; et al.
Abstract: Aim: To conduct an analysis to assess whether the completion of recommended diabetes care processes (glycated haemoglobin [HbA1c], creatinine, cholesterol, blood pressure, body mass index [BMI], smoking habit, urinary albumin, retinal and foot examinations) at least annually is associated with mortality. Materials and methods: A cohort from the National Diabetes Audit of England and Wales comprising 179 105 people with type 1 and 1 397 790 people with type 2 diabetes, aged 17 to 99 years on January 1, 2009, diagnosed before January 1, 2009 and alive on April 1, 2013 was followed to December 31, 2019. Cox proportional hazards models adjusting for demographic characteristics, smoking, HbA1c, blood pressure, serum cholesterol, BMI, duration of diagnosis, estimated glomerular filtration rate, prior myocardial infarction, stroke, heart failure, respiratory disease and cancer, were used to investigate whether care processes recorded January 1, 2009 to March 31, 2010 were associated with subsequent mortality. Results: Over a mean follow‐up of 7.5 and 7.0 years there were 26 915 and 388 093 deaths in people with type 1 and type 2 diabetes, respectively. Completion of five or fewer, compared to eight, care processes (retinal screening not included as data were not reliable) had a mortality hazard ratio (HR) of 1.37 (95% confidence interval [CI] 1.28‐1.46) in people with type 1 and 1.32 (95% CI 1.30‐1.35) in people with type 2 diabetes. The HR was higher for respiratory disease deaths and lower in South Asian ethnic groups. Conclusions: People with diabetes who have fewer routine care processes have higher mortality. Further research is required into whether different approaches to care might improve outcomes for this high‐risk group.